Optimal On-Line Walking Pattern Generation for Biped Robots - Chen, Hao; Pan, Shuwen; Xiong, Rong; Wu, Jun (2010 First International Conference on Networking and Distributed Computing, 2010)
A new 2D walking pattern generation method is proposed for biped robots in this paper. The key feature of the proposed method is to obtain an optimal walking pattern on-line with the largest stability in the sense of zero moment point (ZMP) subject to the constraints of torque and velocity of the joint actuators. With the aids of a 3-link dynamic model of the robot legs and third-order spline interpolation, the hip and foot trajectories of biped robots are generated and the analytical objective function of ZMP as well as constraints of joint torques and angular velocities are obtained in terms of a parameter set. A nonlinear optimization procedure is then applied to obtain the optimal parameter set for the generation of walking pattern. An illustrative example is provided to demonstrate the merits of the proposed method.